2016
DOI: 10.1183/20734735.000716
|View full text |Cite
|
Sign up to set email alerts
|

Common respiratory conditions of the newborn

Abstract: Key pointsRespiratory distress is a common presenting feature among newborn infants.Prompt investigation to ascertain the underlying diagnosis and appropriate subsequent management is important to improve outcomes.Many of the underlying causes of respiratory distress in a newborn are unique to this age group.A chest radiograph is crucial to assist in diagnosis of an underlying cause.Educational aimsTo inform readers of the common respiratory problems encountered in neonatology and the evidence-based management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 96 publications
1
81
1
5
Order By: Relevance
“…This is congruent with findings from a recent study by Mengesha et al [20], where preterm delivery was an independent predictor of neonatal mortality in Northern Ethiopia. This could be explained by the fact that preterm and postterm babies are unable to adjust to extrauterine life and therefore are prone to specific complications like breathing difficulties, intracranial bleeding, infections, hypothermia, and jaundice [21]. This study also found an influence of pregnancy complications on child survival.…”
Section: Maternal Factors Influencing Neonatal Mortalitymentioning
confidence: 53%
“…This is congruent with findings from a recent study by Mengesha et al [20], where preterm delivery was an independent predictor of neonatal mortality in Northern Ethiopia. This could be explained by the fact that preterm and postterm babies are unable to adjust to extrauterine life and therefore are prone to specific complications like breathing difficulties, intracranial bleeding, infections, hypothermia, and jaundice [21]. This study also found an influence of pregnancy complications on child survival.…”
Section: Maternal Factors Influencing Neonatal Mortalitymentioning
confidence: 53%
“…Também a capacidade respiratória do recém-nascido para se adaptar ao ambiente extrauterino é crítica para a sobrevivência. As disfunções respiratórias neonatais podem surgir por várias razões: adaptação atrasada ou má adaptação para a vida extrauterina; condições já existentes (anomalias congênitas ou cirúrgicas) ou adquiridas (infecções pulmonares ocorridas pré ou pós-parto) (13) .…”
Section: Discussionunclassified
“…Respiratory distress is a common condition in neonates requiring admission in a neonatal care unit (NCU) [1]. It can occur in both preterm and full-term neonates affecting both morbidity and mortality rates [2,3]. The main medical diagnoses that are related to these conditions are transient tachypnea, meconium inhalation syndrome, respiratory distress syndrome also known as hyaline membrane disease and pneumonia [4].…”
Section: Introductionmentioning
confidence: 99%